Sampling grid size for characterization of the spatial variability of phosphorus and potassium in an Oxisol - Cherubin, Mauricio Roberto; Santi, Antônio Luis; Eitelwein, Mateus Tonini; Amado, Telmo Jorge Carneiro; Simon, Diego Henrique; Damian, Júnior Melo (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the accuracy in the characterization of the spatial variability of soil phosphorus and potassium, using different sampling grid sizes, as well as the similarity of the thematic maps generated. The study was carried out in a 41.96 ha Oxisol area in the municipality of Boa Vista das Missões, in the state of Rio Grande do Sul, Brazil. Soil sampling was done at the 0.00–0.10 m layer, using seven sampling grid sizes: 50x50, 75x75, 100x100, 125x125, 150x150, 175x175, and 200x200 m. P and K data were subjected to descriptive statistics and geostatistical analyses, and the similarity of the thematic maps generated was analyzed by the coefficient of relative deviation and Pearson’s correlation matrix. The reduction in the size of the sampling grid increases the accuracy in the characterization of the spatial variability of P and K and, consequently, the information generated by the thematic maps. Sampling grid sizes ≤100x100 m are recommended for soil sampling plans adopted in precision agriculture areas in the state of Rio Grande do Sul, Brazil.
Keywords: variable‑rate fertilization; precision agriculture; georeferenced soil sampling; soil fertility; similarity of thematic maps